Pengaruh Metode Bagian Terhadap Hasil Pembelajaran Passing Bawah Bola Voli Siswa Kelas 4 SDN Barutunggul 04 Kabupaten Bandung: Penelitian - Mochamad Rivaldi Yuana Prayoga; Dian Permana; Agung Praseptiana Putra (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aimed to determine the effect of the section method on the learning outcomes of volleyball underhand passing among fourth-grade students at SDN Barutunggul 04, Bandung Regency. The section method is a learning technique that divides skills into several smaller stages before teaching the overall movement, thus improving students' understanding and skills in underhand passing. The results showed that the section method had a significant positive effect on improving volleyball underhand passing learning outcomes. Students who learned using the section method showed greater improvement in basic underhand passing techniques. This study used an experimental method with a One-Group Pretest-Posttest Design. Twenty students were sampled, therefore, non-probability sampling was used. An observation sheet was used as a guideline in conducting the study, to obtain data on the alignment between the plan and its implementation, and to measure the expected changes. The subjects observed in this study were fourth-grade students at SDN Barutunggul 04. Data analysis used a t-test to identify significant differences.